Practical micro-finance - Harper, Malcolm (New Delhi, 2007)
This immensely practical manual is designed to improve the quality and content of micro-finance training programmes, and thereby contribute to the greater availability of affordable, accessible, and mutually profitable financial services to the poor. Malcolm Harper provides step-by-step descriptions for 22 training sessions spread over ten days. He covers all the important topics including sustainability, interest rates, gender issues, delivery methods, impact assessment, and delinquency management. The author includes case studies, quantitative exercises, and suggestions for field visits.
Keywords: Micro finance